2023
DOI: 10.1002/anie.202310838
|View full text |Cite
|
Sign up to set email alerts
|

NIR‐II Absorbing Monodispersed Oligomers Based on N−B←N Unit

Jin Xu,
Yingze Zhang,
Jun Liu
et al.

Abstract: Organic molecules with near‐infrared II (NIR II) light absorption are essential for many biological and opto‐electronic applications. Herein, we report monodispersed oligomers as NIR II light absorber using a new molecular design strategy of resonant N−B←N unit, i.e. balanced resonant boron‐nitrogen covalent bond (B−N) and boron‐nitrogen coordination bond (B←N). We synthesize a series of monodispersed oligomers with thiophene‐fused 4,4‐difluoro‐4‐bora‐3a,4a‐diaza‐s‐indacene (TB), which contains resonant N−B←N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…87,88 Recently, Liu and co-workers developed a series of monodisperse thiophene-fused BODIPY oligomers. 89 Theoretical calculations revealed that the resonant N−B ← N units effectively decreased the aromaticity of the aromatic rings and thus improved π delocalization in the oligomers, resulting in intense absorption in the NIR-II region (with an absorption maximum of 1169 nm). Moreover, the potential of thiophenefused BODIPY tetramer as an electron acceptor for NIR-II organic photodetectors (OPDs) was demonstrated, showing a specific detectivity of 2.98 × 10 11 Jones at 1180 nm under zero bias.…”
Section: Coordinate B ← N Bondmentioning
confidence: 99%
See 1 more Smart Citation
“…87,88 Recently, Liu and co-workers developed a series of monodisperse thiophene-fused BODIPY oligomers. 89 Theoretical calculations revealed that the resonant N−B ← N units effectively decreased the aromaticity of the aromatic rings and thus improved π delocalization in the oligomers, resulting in intense absorption in the NIR-II region (with an absorption maximum of 1169 nm). Moreover, the potential of thiophenefused BODIPY tetramer as an electron acceptor for NIR-II organic photodetectors (OPDs) was demonstrated, showing a specific detectivity of 2.98 × 10 11 Jones at 1180 nm under zero bias.…”
Section: Coordinate B ← N Bondmentioning
confidence: 99%
“…The skeleton of 42 was further utilized as a building block for constructing small-band gap conjugated polymers, which provided new strategies for the design of NIR-absorption materials . This resonant N–B ← N unit has also been observed in BODIPY compounds, which have been applied in various fields because of the excellent stability and interesting photophysical properties. , Recently, Liu and co-workers developed a series of monodisperse thiophene-fused BODIPY oligomers . Theoretical calculations revealed that the resonant N–B ← N units effectively decreased the aromaticity of the aromatic rings and thus improved π delocalization in the oligomers, resulting in intense absorption in the NIR-II region (with an absorption maximum of 1169 nm).…”
Section: Effect Of Different Bn-doping Modesmentioning
confidence: 99%
“…We have referred to it as the resonant N–B←N unit in our recent studies . We have found that the resonant N–B←N unit leads to downshifted E LUMO and minimized band gap of the resulting molecules/polymers. , This motivates us to use BODIPY as the building block to design conjugated polymers with an ultrasmall band gap and low-lying E LUMO .…”
Section: Introductionmentioning
confidence: 99%
“…42 We have found that the resonant N−B←N unit leads to downshifted E LUMO and minimized band gap of the resulting molecules/polymers. 43,44 This motivates us to use BODIPY as the building block to design conjugated polymers with an ultrasmall band gap and low-lying E LUMO . In this work, we report a conjugated copolymer of alternating BODIPY unit and vinylene, P-α-V (see Scheme 1), which shows an ultrasmall band gap and excellent electrontransporting property.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Near-infrared (NIR, 780–3000 nm) organic photodetectors (OPDs) have drawn tremendous attentions due to their inherent advantages such as being lightweight, flexible, and compatible with large-area, low-cost fabrication processes, enabling great application potential in sensing, optical communication, medical imaging, artificial intelligence, surveillance, etc. Generally, the responsivity ( R ) and detectivity ( D *) values at certain wavelength regions are recognized as two key figures of merit for evaluating the performance of OPDs. In the past few years, NIR OPDs possessing comparable R and D * values with silicon photodetectors within the wavelength of 1000 nm have been realized owing to the substantial development of various narrow-bandgap nonfullerene acceptors (NFAs) and high-performance conjugated polymer (CP) donors. However, NIR OPDs that simultaneously achieve high R and D * in the short-wavelength infrared (SWIR) region (1000–1700 nm) have not been fully developed, causing OPD development to lag far behind their inorganic counterparts, such as indium gallium arsenide (InGaAs) photodetectors. Therefore, in the realm of materials development, there is an urgent need to explore effective molecular design strategies for creating novel narrow-bandgap NFAs or CPs for OPDs that exhibit outstanding performance in both R and D * in the wavelength region exceeding 1000 nm.…”
mentioning
confidence: 99%